Influence of Mg dopant on photocatalytic properties of Mg-doped ZnO nanoparticles prepared by sol-gel method - Sudarat Sitthichai (2018)
© 2017 The Ceramic Society of Japan. All rights reserved. Mg-doped ZnO nanoparticles with different Mg contents were synthesized by sol-gel method with subsequently calcination at 600°C for 2h. The X-ray diffraction results revealed the presence of wurtzite pure ZnO with hexagonal structure in both the undoped and doped samples. The crystallite size of the nanoparticle samples was calculated by Scherrer formula, 92nm for ZnO and 43nm for 5wt% Mg-doped ZnO. Raman spectra of pure and Mg-doped ZnO show peak at 437cm -1 assigned to ZnO nonpolar optical phonon high E 2 mode. The size of Mg-doped ZnO characterized by transmission electron microscopy is much smaller than that of pure ZnO. The photocatalytic properties of ZnO and Mg-doped ZnO were investigated by monitoring the methylene blue degradation under UV radiation. For the present study, the 5wt% Mg-doped ZnO shows the highest photocatalytic activity of 92% within 300 min.